Liver Profile of Atazanavir/Ritonavir in Pregnant Albino Rats - Elias Adikwu; James Kemelayefa; Winifred Ocheiga (Biology, Medicine, & Natural Product Chemistry, 2019)
Medication use during pregnancy is challenging due to the occurrence of maternal or fetal toxicities. Atazanavir/ritonavir (ATV/r) has hepatotoxic potential hence; use in pregnant patients living with human immunodeficiency virus may cause maternal hepatotoxicity. This study assessed the liver profile of ATV/r in pregnant albino rats. Thirty pregnant albino rats randomized into groups were orally treated daily with ATV/r (4.28/1.43 mg/kg-34.3/11.4 mg/kg) for 16 days. After treatment, the rats were weighed and sacrificed. Blood samples were collected and examined for serum biochemical parameters. Liver samples were weighed and assessed for biochemical and histological changes. Body and liver weights were normal (p>0.05) in ATV/r-treated pregnant rats when compared to control. Serum total cholesterol, triglyceride, low density lipoprotein cholesterol and blood glucose levels were significantly (p<0.01) elevated whereas high density lipoprotein cholesterol level was significantly (p<0.01) decreased in rats treated with ATV/r (34.3/11.4 mg/kg) when compared to control. Liver and serum aminotransferases, alkaline phosphatase, gamma-glutamyl transferase, lactate dehydrogenase, total bilirubin, and conjugated bilirubin levels were significantly increased in a dose-dependent fashion in rats treated with ATV/r; 8.57/2.86 mg/kg (p<0.05), 17.1/5.72 mg/kg (p<0.01) and 34.3/11.4 mg/kg (p<0.001) when compared to control. Liver superoxide dismutase, catalase, glutathione and glutathione peroxidase levels were significantly decreased whereas malondialdehyde levels were significantly increased in a dose-dependent fashion in rats treated with ATV/r; 8.57/2.86 mg/kg (p<0.05), 17.1/5.72 mg/kg (p<0.01) and 34.3/11.4 mg/kg (p<0.001) when compared to control. Necrotic hepatocytes were observed at higher doses of ATV/r. ATV/r may not be hepatotoxic in pregnant women living with HIV at the clinical dose.